Experimental Pengukuran Volume Tanki Bahan Bakar Di Kapal Dengan Metode Simson I Dan Simson II - Kurniawan, Ratna Dwi; P, Budi (Marine Science and Technology Journal; Vol 2 No 1 (2021): Marine Science and Technology JournalDO - 10.31331/maristec.v2i1.1772, 2021)
A ship is a floating Structure that moves and is used in  water ttransportation, to good manouvering, and  to get a certain speed with propulsion efficiency, ship hull is commonly streamlined and  designed so that obstacles or frictional forces with water are small, streamline forms in general the shape follows the flow of  fluid or water so that the shape of the hull is curved. With a curved shape, the shape of the room inside also follows the hull of the ship, as well as the shape of the fuel tank, lubricant tank , fresh water tanks, liquid cargoes are also curved / curved or not square, tubes that are easy to determine volume. This volume calculation needs to be done carefully because it involves the need for fuel, fresh water, lubricants that will be needed during the trip in order to ensure that the needs are fulfilled until the destination. There are several methods for determining the area and volume of a curved plane, such as trapezium, simson etc. In carrying out measurements, students often have difficulty in understanding the method of measuring the area and volume of curved spaces on the ship, so it is necessary to make a real model, From the experimental results, it is known that for Samson's rule 1 there is a volume difference of almost 8%, for Samson II's rule it is 6%.